Synthesis of Nitrogen-Doped Porous Carbon Nanocubes as a Catalyst Support for Methanol Oxidation - Liang, Y.; Wei, J.; Zhang, X.; Zhang, Jin; Jiang, San Ping; Wang, H. (WILEY-V C H VERLAG GMBH, 2016)
Nitrogen-doped porous carbon nanocubes with a high surface area synthesized by carbonizing Prussian blue nanocubes coated with poly(fururyl alcohol) were used to support Pt nanoparticles as an electrocatalyst for the oxidation of methanol. The resulting catalyst exhibited excellent electrocatalytic activity and electrochemical stability, owning to its high surface area, a uniform dispersion of Pt particles, and enhanced interaction between the particles and the support.